Proceedings of the 17th ACM Great Lakes Symposium on VLSI 2007
DOI: 10.1145/1228784.1228840
|View full text |Cite
|
Sign up to set email alerts
|

An automated unique tagging system using CMOS process variation

Abstract: An Automated Unique Tagging System (AUTS) is presented, intended for RFID applications, that generates identification numbers based on random process variations, circumventing the need for non-volatile memories such as EEPROM or Flash. A sense amplifier is used to measure the mismatch in threshold voltage between two identical NMOS devices and generate a 1-bit random output. The AUTS has been fabricated in the TSMC 0.25µm CMOS process and tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, for such systems, wireless communication is frequently the largest energy consumer, so any reduction in transmitted data directly improves system performance. It has been observed that prior knowledge of which bits are unreliable can be used to increase the accuracy of identification [15,18], and that the reliability of individual bits can be determined by examining the magnitude of the underlying variation [17].…”
Section: System Overview and Designmentioning
confidence: 99%
“…However, for such systems, wireless communication is frequently the largest energy consumer, so any reduction in transmitted data directly improves system performance. It has been observed that prior knowledge of which bits are unreliable can be used to increase the accuracy of identification [15,18], and that the reliability of individual bits can be determined by examining the magnitude of the underlying variation [17].…”
Section: System Overview and Designmentioning
confidence: 99%
“…This reduces the amount of data that needs to be transmitted, and thus the energy consumption of the sensor. It has been observed that prior knowledge of which bits are unreliable can be used to increase the accuracy of identification [35] [41], and this system is novel in its ability to characterize the value and reliability of each random bit using only two read operations. It does this by examining the amount of manufacturing variation on which each bit is based, and determining if it is large enough to outweigh the effects of electrical noise.…”
Section: Previous Workmentioning
confidence: 99%